The age of entrepreneurship education research : evolution and future - Corbett, Andrew C.; Marino, Louis D.; Alsos, Gry A. (Advances in entrepreneurship, firm emergence and growth, 2023)
There have been significant advances in entrepreneurship education pedagogy over the last two decades. However, a gap remains with many questions about exactly what we should be teaching in the classroom and how we should be teaching it. Stakeholders of all types - students, parents, employers, accrediting bodies, and government officials - are all looking for clarity, transparency, and a stronger sense of exactly what should encompass an entrepreneurship education. What should the outcome of entrepreneurship courses and programs be? What are we currently teaching? What should we be teaching? And, how should we be teaching it, are just some of the foundational questions addressed in The Age of Entrepreneurship Education Research. The collection of renowned entrepreneurship education researchers explores topics such as the theory of ideation, how to develop an expertise approach, how to reimagine entrepreneurship education to promote gender equality, how to activate an entrepreneurial mindset for neuro-diverse students, and more. The volume is bookended with an opening chapter that traces the evolution of entrepreneurship education research and a closing one that looks toward the future. This volume is of great interest to both teachers and students and practitioners in entrepreneurship, business and education.